Measuring Iron Oxide Composites with a Custom-Made Scanning Magnetic Microscope - Christian D. Medina; Leonardo A. F. Mendoza; Cleânio Luz-Lima; Antonio C. Bruno; Jefferson F. D. F. Araujo (Sensors)
We improved a scanning magnetic microscope built previously by adding a new detection system and the capability of mapping samples applying magnetic fields from −500 mT to +500 mT. The mechanical structure was also enhanced to decrease vibrations of the system in the earth’s magnetic field. The microscope is based on a differential arrangement of two Hall effect elements. The overall system presented a sensitivity of about 850 <semantics>nTrms√Hz</semantics>, and it was calibrated using a 99% pure nickel sphere. The system achieved a magnetic moment sensitivity of the order of 10 nAm2. All equipment used for operating the magnetic microscope was controlled by using the LabVIEW® platform. We also fabricated samples with controlled properties using iron oxide microparticles and epoxy resin with various densities. We obtained the magnetization curves of the composites using the assembled microscope and compared them with the iron oxide powder.